Inter-arm Blood Pressure Difference as an Emergent Risk for Pre-hypertension - Javaria Manzoor; Muhammad Absar Alam; Rooha Tariq (Aziz Fatimah Medical and Dental College, 2019)
Objective: This study was aimed to determine the frequency of pre-hypertension and hypertension along with its association with inter-arm difference of blood pressure. Methodology: It was a cross sectional study conducted at Aziz Fatimah Medical and Dental College Faisalabad. Students of age ranged 19-21 years were enrolled by convenience sampling technique for screening of pre-hypertension and hypertension. Blood pressure was recorded from both arms by using sphygmomanometer and inter-arm differences were estimated. Mean±SD for continuous variables, frequency and percentages for categorical variables and chi square for association between pre-hypertension, hypertension and inter-arm difference was analyzed by SPSS 21. Results: Study comprised of 100 students with mean age 19.79±1.18 years. Of total 47% were females and 53% was male population. Mean systolic (p value =0.0002*) and diastolic (p value =0.000*) blood pressure of the two arms were significantly different. Of total population, 27% and 13% of population had pre-hypertension and hypertension respectively. Mean systolic inter-arm difference was significantly higher among the hypertensive subjects as compared to pre-hypertensive subjects, (p value =0.0001*). No significant difference was noted with respect to diastolic inter-arm difference (p value =0.93). Greater percentage of normotensive subjects have systolic inter-arm difference <10mmHg as compared to this most of the subjects with hypertension and pre-hypertension have systolic inter-arm difference of >15mmHg. Significant association between hypertension and systolic inter-arm difference was noted (p value =0.025) Conclusion: Pre-hypertension and hypertension is prevalent among young adults. High systolic inter-arm difference was significantly associated with pre-hypertension and hypertension.